2017
DOI: 10.1172/jci.insight.92979
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin expression by keratinocytes controls local and systemic inflammation

Abstract: Tristetraprolin (TTP, encoded by the Zfp36 gene) regulates the mRNA stability of several important cytokines. Due to the critical role of this RNA-binding protein in the control of inflammation, TTP deficiency leads to the spontaneous development of a complex inflammatory syndrome. So far, this phenotype has been largely attributed to dysregulated production of TNF and IL‑23 by myeloid cells, such as macrophages or DCs. Here, we generated mice with conditional deletion of TTP in keratinocytes (Zfp36fl/flK14-Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 49 publications
6
37
0
Order By: Relevance
“…By studying transgenic mice with the deletion of tristetraprolin (TTP/Zfp36; a keratinocyte-specific gene), Andrianne et al [78] illustrate how TTP acts as an RNA-binding protein that downregulates the expression of genes that encode proinflammatory cytokines in the skin epidermis. Such mice developed a psoriasiform phenotype associated with a strong inflammatory reaction.…”
Section: Resultsmentioning
confidence: 99%
“…By studying transgenic mice with the deletion of tristetraprolin (TTP/Zfp36; a keratinocyte-specific gene), Andrianne et al [78] illustrate how TTP acts as an RNA-binding protein that downregulates the expression of genes that encode proinflammatory cytokines in the skin epidermis. Such mice developed a psoriasiform phenotype associated with a strong inflammatory reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The LysM-Cre mouse model has successfully been used to study the role of specific genes in myeloid cells in the bone marrow (28), the lungs (29), the liver (30), the gut and the skin (31,32). However, LysM-cre does not seem to be effective in deleting genes in splenic myeloid cells during VL.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with previous reports in other tissues. For instance, massive infiltration of neutrophils has been shown to occur in the skin of TTP KO mice subjected to psoriasis-like inflammation ( 30 ), whereas reduced airway neutrophilic infiltration was shown in mice genetically modified to express constitutively active endogenous unphosphorylated TTP following challenge with cigarette smoke ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contribution of non-HPC-specific TTP toward modulation of inflammatory responses has also been suggested in previous reports. For instance, TTP regulation of TNF in keratinocytes, but not in myeloid or dendritic cells, was shown to protect mice from exacerbation of psoriasis-like pathology, development of spontaneous systemic inflammation, and dactylitis ( 30 ). Another study suggested a role of intestinal epithelial cell-specific TTP in exacerbation of acute colitis ( 49 ).…”
Section: Discussionmentioning
confidence: 99%